2015
DOI: 10.1136/injuryprev-2014-041468
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the fall-injury reducing effect of impact absorbing flooring among female nursing home residents: initial results

Abstract: This is, to our knowledge, the first study evaluating the injury-reducing effect of impact absorbing flooring in a nursing home showing statistically significant effect. The results from this study are promising, indicating the considerable potential of impact absorbing flooring as a fall-related injury intervention among frail elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 33 publications
1
34
1
Order By: Relevance
“…It had also been tested concerning impact reduction during lateral falls on the pelvis, showing an overall protective effect, especially for frail elderly (Bhan, Levine, & Laing, 2013). We previously evaluated the injury reducing effect of the floor and found it to decrease the risk of injury by 59% for falls on compliant flooring compared to regular flooring (Gustavsson, Bonander, Andersson, & Nilson, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…It had also been tested concerning impact reduction during lateral falls on the pelvis, showing an overall protective effect, especially for frail elderly (Bhan, Levine, & Laing, 2013). We previously evaluated the injury reducing effect of the floor and found it to decrease the risk of injury by 59% for falls on compliant flooring compared to regular flooring (Gustavsson, Bonander, Andersson, & Nilson, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that floor characteristics and floor materials could influence the injury severity of falls in older adults. [7][8][9][10][11][12] However, floor factors associated with injury severity from outdoor falls in older adults have never been studied. We hypothesized that floor factors might affect severe fall injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Recent preliminary studies suggest that compliant flooring may reduce fall-related injuries in LTC,36 37 but these studies have used retrospective36 and non-randomised36 37 study designs, which leave open the opportunity for biased effect estimates, and they have been insufficiently powered to examine the effect of compliant flooring on the most serious and costly fall-related injuries. The FLIP Study will fill this gap in the evidence base.…”
Section: Discussionmentioning
confidence: 99%
“…While two falls on standard flooring resulted in fracture, no falls on compliant flooring resulted in fracture 36. Further, a non-randomised study of female residents at a Swedish LTC site installed compliant flooring (1.25 cm Kradal) in 350 m 2 of a single ward, including some resident rooms and common areas but no bathrooms 37. During 2.5 years of prospective falls surveillance, 16.9% of falls (13 of 77) on compliant flooring were injurious compared with 30.3% of falls (77 of 254) on control flooring (vinyl, linoleum and ceramic tile, all with concrete underlay), which resulted in a significant 59% reduction (95% CI 20% to 80%) in risk for fall-related injury after adjustment for individual-level covariates.…”
Section: Introductionmentioning
confidence: 99%